Pengaruh Promosi dan Kualitas Produk terhadap Keputusa Pembelian The Botol Sosro Pada Konsumen Ayam Penyet Putri - Fitri Puspita Sari; Riandani Rezki Prana (CIVITAS: Jurnal Studi Manajemen, 2022)
The purpose of this research is to know how much influence promotion and product quality to purchasing decisions teh botol sosro on ayam penyet putri. The sampel was 136 respondens who visited the ayam penyet putri. Sampling using saturated sampling, which is a research method that all populations are used as samples. Data analysis using multiple linier regression test, hypothesis testing using the coefficient of determination (R2), simultaneous test (F test) and partial test (t test) with data processing using SPSS version 24.00 .The results showed that simultaneously independent variables is Promotion and Product Quality have positive and significant effect to Purchasing Decision. In partial, Promotion have positive and significant effect to Purchasing Decision, while the variable Product Quality showed that have positive and significant effect to Purchasing Decision Teh Botol Sosro on Ayam Penyet Putri.